Psychological side effects of hormonal contraception: a disconnect between patients and providers - Sarah Martell; Christina Marini; Cathy A. Kondas; Allison B. Deutch (BMC, 2023)
Abstract Background Existing literature about the psychological side effects of hormonal contraception (HC) is limited. The goal of this study is to better characterize patients' subjective experiences with HC, its side effects, and contraception counseling. Methods This is a cross-sectional, survey-based study using a convenience sample of patients who had used HC at some point in their lives. Recruitment occurred from June 2021-February 2022. Results Of the 188 responses included in the analysis, 43.6% reported experiencing mood changes as a side effect of HC at some point in their lives. The most common reason participants cited for discontinuing or switching contraception methods was side effects (48.3%). Participants with a history of psychiatric illness were significantly more likely to report mood changes as a side effect of their HC (61.2%) compared to participants with no history of psychiatric illness (29.5%). Among patients with a history of psychiatric illness, 38.8% responded that their psychiatric symptoms worsened with HC while only 11.2% responded that their symptoms improved with HC. The majority (83%) of participants responded that their provider never mentioned the possibility of psychological side effects during contraception counseling. If/when they experienced side effects associated with their HC, 22.7% of participants disagreed that their provider adequately addressed their concerns. Conclusion These findings suggest that mood changes may be among the most common perceived side effects of HC and speak to a disconnect between patients and providers when it comes to discussing the possibility of psychological side effects with HC.